School success for at-risk students : a culturally responsive tiered approach - Cumming, Therese M. (Routledge, 2019)
"School Success for At-Risk Students: A Culturally Responsive Tiered Approach introduces a model that incorporates cultural responsiveness into the familiar three-tiered model of behavioural and academic support. The model is designed to modify learning environments to support all students, identify students at risk, and provide a continuum of supports for those who need it. This book is a necessary companion for educators and researchers who have an interest in exploring the nature and context of educating at-risk students from the perspective of a culturally responsive multi-tiered system of support" --